On the response of flax fiber reinforced composites under salt-fog/dry conditions: Reversible and irreversible performances degradation. (1st February 2022) - Fiore, V.; Calabrese, L.; Miranda, R.; Badagliacco, D.; Sanfilippo, C.; Palamara, D.; Valenza, A.; Proverbio, E.
Abstract: Despite their scarce resistance to humid or wet conditions, natural fiber reinforced composites (NFRCs) seem to be able to partially recover their performances under discontinuous exposition to marine environment. To investigate this peculiarity, flax fiber reinforced composite was at first subjected to salt-fog spray condition at 35 °C for 15 and 30 days, respectively, and then stored in ''dry" condition (i.e., 50% R.H. and 22 °C) between 0 and 21 days. The performances evolution was evaluated through flexural tests, water uptake and contact angle measurements. Moreover, the morphology of fractured mechanical samples was examined by using 3D optical microscope and scanning electron microscope (SEM). Flax fiber reinforced composite experienced phenomena of both reversible and irreversible degradation during the wet phase thus evidencing a relevant mechanical recovery thanks to the drying. Quite interestingly, the laminate showed an almost complete recovery of the flexural strength, meaning that this property is more strictly related to mainly reversible aging phenomena whereas the greater stiffness loss is more probably due to irreversible ones. Highlights: Natural Fiber Reinforced Composites were aged under alternated salt-fog and dry steps. Flexural tests, water uptake and water contact angle measurements were performed. NFRCs experienced reversible and irreversible degradative phenomena. Due to the drying, NFRCs showed an almost complete recovery of flexural strength. A topological map discriminating reversible and irreversible aging zones was created.